Interpretasi Kebenaran dalam Ruang Digital: Telaah Hermeneutika Paul Ricoeur - Fernandes, Stefanus; Mengkala, Dian Labo; Vianey, Oktafiana Blandina (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2025)
The focus of this study is “Interpreting Truth in the Digital Space: A Hermeneutic Analysis of Paul Ricoeur”, analyzed through various written sources. This study explores how the concept of truth in the digital realm can be understood through the lens of Paul Ricoeur’s hermeneutics. The research employs critical reading and textual analysis as its methodology. This approach examines the concept of truth in relation to Paul Ricoeur’s philosophy, particularly in the context of the digital space, which increasingly dominates the process of meaning-making and interpretation. This study finds that digital device users can easily produce news that often contradicts reality. Fake news and hate speech are frequently perceived as legitimate and accepted as truth, ultimately compromising the very foundation of shared life. The dominance of digital media has reshaped truth standards—not only as a supporting tool but also as a factor that can hinder and even distort the understanding of truth. Paul Ricoeur’s hermeneutic philosophy offers an approach to understanding this phenomenon. As a theory of interpretation, hermeneutics plays a role in uncovering implicit meanings and clarifying ambiguous messages. Therefore, issues in the digital space can be addressed more wisely, depending on how individuals interpret the information presented by digital media. This study reveals that while the digital space provides freedom of expression, it also presents new challenges in understanding truth. The dominance of digital media in shaping public opinion has the potential to erode the very meaning of truth. Thus, Paul Ricoeur’s hermeneutic perspective can serve as a bridge for navigating the complexities of interpretation in the digital age, helping individuals critically assess and filter information.